Dysfunctional Breathing in Children: A Literature Review - Georgia Karkouli; Konstantinos Douros; Dafni Moriki; Paraskevi Moutsatsou; Ioanna Giannopoulou; Eirini Maratou; Despoina Koumpagioti (MDPI AG, 2024)
Dysfunctional breathing (DB) describes a respiratory condition that is mainly characterized by abnormal breathing patterns, affecting both children and adults, often leading to intermittent or chronic complaints and influencing physiological, psychological, and social aspects. Some symptoms include breathlessness; dizziness; palpitations; and anxiety, while its classification lies in breathing pattern disorders and upper airway involvement. Its prevalence among the pediatric population varies with a female overrepresentation, while the existence of comorbidities in DB, such as asthma, gastro-esophageal reflux, nasal diseases, and anxiety/depression, frequently leads to misdiagnosis or underdiagnosis and complicates therapeutic approaches. The basic diagnostic tools involve a detailed history, physical examination, and procedures such as structured light plethysmography, cardiopulmonary exercise testing, and laryngoscopy when a laryngeal obstruction is present. The management of DB presumes a multidimensional approach encompassing breathing retraining, disease-specific advice through speech and language therapy in the presence of laryngeal obstruction, psychotherapy for fostering self-efficacy, and surgical therapy in a structural abnormality. The current review was developed to provide a summary of classifications of DB and epidemiological data concerning the pediatric population, comorbidities, diagnostic tools, and therapeutic approaches to enhance the comprehension and management of DB in children.